Nutritional composition and sensory quality evaluation of Philippine Choco Chiffon Cake / Raymund B. Moreno. - Moreno, Raymund B. (Universiti Teknologi Mara Selangor, 2019)
This study was conducted to determine the nutritional composition, sensory qualities, and general acceptability of the chiffon cake with different levels of cacao (Theobroma cacao Linn.) powder. There were five different samples labeled A, B, C, D and E with ratios of 100:0, 90:10, 80:20, 70:30, 60:40, respectively: each representing the percentage of wheat flour and cacao flour mixed together to produce the flour mixtures. Treatment A has a pure 100 % wheat flour sample and served as the control. Based on the results of nutritional analysis, the percentage of moisture content, ash, crude protein, total fat, carbohydrate and energy were 34.6 %, 1.33 %, 5.71 %, 13.5 %, 44.9% and 324 Kcal respectively for Treatment B - composed of 90 % wheat flour and 10 % cacao powder -which happened to be the most acceptable treatment based on the sensory evaluation conducted. In majority, the sensory acceptability level of chiffon cake enriched with different levels of cacao bean powder in terms of appearance, aroma, texture, taste and general acceptability were ranged from liked very much to like extremely. The findings of this study will definitely be beneficial to health-conscious consumers since it will fortify the ingredients for making chiffon cake - going on a healthier and guilt-free path. After all, the results of adding cocoa powder into chiffon cake aimed to make a baseline database - using the information obtained - which will be beneficial for further studies and/or other parallel researches.